2021
DOI: 10.1177/10742484211023639
|View full text |Cite
|
Sign up to set email alerts
|

ClC-3: A Novel Promising Therapeutic Target for Atherosclerosis

Abstract: Chloride channel 3 (ClC-3), a Cl−/H+ antiporter, has been well established as a member of volume-regulated chloride channels (VRCCs). ClC-3 may be a crucial mediator for activating inflammation-associated signaling pathways by regulating protein phosphorylation. A growing number of studies have indicated that ClC-3 overexpression plays a crucial role in mediating increased plasma low-density lipoprotein levels, vascular endothelium dysfunction, pro-inflammatory activation of macrophages, hyper-proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 100 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…In contrast with that of ClC-3 −/− mice consuming a high-fat diet ( Ma et al, 2019 ), there were no significant differences in blood lipids between ClC-3 −/− and ClC-3 +/+ mice with a normal diet at the age of 12 weeks; intraperitoneal glucose tolerance test demonstrated that ClC-3 deletion delayed the response to blood glucose increasing and enhanced the efficiency of lowering blood glucose once started ( Figure 2 ). ClC-3 −/− mice had a partial impairment of glucose tolerance in the condition of ad libitum self-feeding normal diet, which may be associated with the inhibition of insulin secretion by ClC-3 knocking out ( Barg et al, 2001 ; Deriy et al, 2009 ; Li et al, 2009 ; Niu et al, 2021 ). This finding appeared to be inconsistent with the improvement of glucose tolerance impairment in ClC-3 −/− mice with obesity or diabetes ( Huang et al, 2014 ; Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with that of ClC-3 −/− mice consuming a high-fat diet ( Ma et al, 2019 ), there were no significant differences in blood lipids between ClC-3 −/− and ClC-3 +/+ mice with a normal diet at the age of 12 weeks; intraperitoneal glucose tolerance test demonstrated that ClC-3 deletion delayed the response to blood glucose increasing and enhanced the efficiency of lowering blood glucose once started ( Figure 2 ). ClC-3 −/− mice had a partial impairment of glucose tolerance in the condition of ad libitum self-feeding normal diet, which may be associated with the inhibition of insulin secretion by ClC-3 knocking out ( Barg et al, 2001 ; Deriy et al, 2009 ; Li et al, 2009 ; Niu et al, 2021 ). This finding appeared to be inconsistent with the improvement of glucose tolerance impairment in ClC-3 −/− mice with obesity or diabetes ( Huang et al, 2014 ; Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ClC-3 chloride channels are widely expressed in most mammalian cells and are primarily localized on cell and organelle membranes. Regarding the important roles in the vasculature’s pathological changes, ClC-3 was considered a promising therapeutic target for cardiovascular diseases (CVDs) ( Duan, 2011 ; Du and Guan, 2015 ; Niu et al, 2021 ). It is well known that diabetes, dyslipidemia, and hypertension are CVDs’ most common risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…HDL has been shown to protect against LDL oxidation, thereby preventing the generation of proinflammatory oxidized lipids ( 23 ). Notably, Clcn3 deficiency prevents atherosclerotic lesion development in ApoE −/− mice ( 24 ). The results depicted in Figure 3 proved that the knockout of Clcn3 caused a decrease in LDL levels among mice fed with HFD.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most abundant anions in organisms, chloride ions regulate a very wide range of physiological activities. The ClC-3 chloride channels, a kind of voltage-gated anion channel, participates in ion homeostasis, the regulation of cell volume, acidification of the internal environment, proliferation, apoptosis and many other processes in biological systems [ 4 , 5 ]. Recent studies have found that ClC-3 chloride channels are closely related to bone metabolism.…”
Section: Introductionmentioning
confidence: 99%